MANET – A cogitation of its design and security issues - Olanrewaju, Rashidah Funke; Khan, Burhan ul Islam; Anwar, Farhat; Khan, Abdul Raouf; Ahmed Shaikh, Faraz; Mir, Mohammad Shuaib (IDOSI Publications, 2016)
With the fast proliferation of wireless devices e.g., cell phones, PDAs, laptops, wireless sensors, etc., the significance of wireless communication especially mobile adhoc networking is quite evident. The need to shun dependency on fixed infrastructure networks led to the evolution of Mobile Adhoc Network (MANET). MANETs have numerous advantages like dynamic topology, lack of centralization, speedy and affordable installation, etc. but the features of MANETs impart certain complications as well such as unreliability caused due to node mobility, bandwidth constraints of the wireless link making it vulnerable to attacks, lack of standardization of security solutions, etc. Notably, security in MANETs is a challenge to researchers. In this paper, an overview of MANETs is provided followed by a critical account of the relevant review work that has been carried out so far in this domain. This paper tries to highlight the various issues in the design and security requirements of MANETs. As such, the proposed study revolves around all the security aspects of mobile adhoc networks including routing protocols, mobile agents, malicious nodes, intrusion detection system and other factors that affect the quality of service in MANETs